Engaging Media for Mental Health Applications: the EMMA project - Baños, R; Botella, C; Quero, S; García-Palacios, A; Alcañiz, M (Studies in health technology and informatics, 2011)
EMMA project has been focused on how the sense of presence in virtual environments mediates or generates emotional responses, and how to use presence and emotional responses in virtual environments effectively in clinical and non clinical settings. EMMA project has developed two different virtual environments. The first one acts as a 'mood device' and is aimed to induce and enhance several moods on clinical and non clinical subjects. The second one is a virtual environment that acts as an adaptive display to treat emotional disorders (Post-traumatic Stress Disorder, Adjustment Disorder and Pathological Grief). This virtual world varies the contents that are presented depending on the emotions of the patient at each moment. The goal of this paper is to outline the main goals achieved by this project.